ME-MPS: An MR-MPS-SW extension model for critical software in regulated environments - Machado, Everton; Marques, Johnny (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2023: Anais do XXII Simpósio Brasileiro de Qualidade de Software, 2023)
Safety-critical software puts human lives at risk or can cause significant financial losses in case of failures. Environments regulated by security standards impose requirements on critical software development organizations that aim to guide them in the development process. The MPS.br Reference Model for Software (MR-MPS-SW) aims to increase the quality of the software process of a wide range of Brazilian companies, small and medium-sized, from varied niches, being, therefore, a generalist model of high applicability and low application domain specificity. This work proposes the ME-MPS, an Extension Model to the MR-MPS-SW that adds Processes and Expected Results to guide entities interested in studying, adapting, or applying the national model in critical software projects. This work also reports the application in a proof of concept adaptation of one of the objectives of the RTCA DO-178C standard, used in software certification in the aviation domain.